SYSTEMATIC REVIEW ON THE EPIDEMIOLOGY AND CLINICAL MANIFESTATIONS OF VARICOSE VEIN DISEASE - BENKE, SAMIKSHA; KORE, PADMAJA SANTOSH (Asian Journal of Pharmaceutical and Clinical Research, 2024)
This article examines the management of varicose vein disease, a condition affecting lower limbs and characterized by swollen, convoluted veins. It highlights that prolonged standing and obesity, particularly in older adults, increase the likelihood of varicose vein disease. It provides a comprehensive analysis of treatment options and preventative strategies. The review discusses varicose veins, their causes, prevention methods, risk factors, and treatments. It highlights the effectiveness of endovascular, surgical, and herbal therapies in improving quality of life and reducing secondary vein-related issues. Lifestyle interventions like consistent yoga and certain fruits and vegetables are also emphasized as preventative strategies. The article emphasizes the importance of antioxidant medications, particularly flavonoid-based ones, in reducing arterial blood pressure and preventing atherosclerosis in patients with varicose veins. These veins, typically found in the thigh or calf, are enlarged due to sensitivity to the venous wall and abnormal valve function. Over time, they may become longer, twisted, pouched, and thicker due to gravity pulls.